2022
DOI: 10.3920/jiff2021.0096
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality evaluationin vivo of cricket flour (Gryllus assimilis) reared in Brazil

Abstract: This study aimed to evaluate the chemical and biological quality of Gryllus assimilis flour, through the analysis of nutritional and biochemical parameters of tests on young rats (Rattus norvegicus – Fischer). The most deficient essential amino acid was methionine, with a chemical score of 56.40%. For the net protein ratio (NPR) and net protein utilisation (NPU) ratio, the diet containing unsupplemented cricket flour was not enough to reach the NPR and NPU levels of the control group and was insufficient to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Net protein ratio (NPR) is determined taking into account the average weight gain of the animals in the test group, weight loss of the animals fed the non-protein diet and the average protein intake. In three studies, no NPR differences were observed between animals that consumed casein and animals in the test groups [12][13][14] Araujo et al, (2020) [15] , found lower NPR values for animals fed with insects.…”
Section: Protein Qualitymentioning
confidence: 92%
See 4 more Smart Citations
“…Net protein ratio (NPR) is determined taking into account the average weight gain of the animals in the test group, weight loss of the animals fed the non-protein diet and the average protein intake. In three studies, no NPR differences were observed between animals that consumed casein and animals in the test groups [12][13][14] Araujo et al, (2020) [15] , found lower NPR values for animals fed with insects.…”
Section: Protein Qualitymentioning
confidence: 92%
“…Regarding the animal model used in the studies, most used rats (n=9; 90%) [6,[9][10][11][12][13][14][15][16] . Only one study was carried out with mice (n=1; 10%) [17] .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations